Optimization of CNC Turning Parameters on Aluminum Alloy 6063 using TaguchiRobust Design. (2018) - Saravanakumar, A.; Karthikeyan, S.C.; Dhamotharan, B.; kumar, V. Gokul
Abstract: The present investigation is to find the optimum turning parameters during machining of aluminum alloy 6063 with carbon nitride inserts. Process parameters considered for this research are feed, speed and depth of cut and were examined with the help of design of experiments to obtain better surface finish and minimize roundness error. Experiments were conducted based on Taguchi method L27 orthogonal array and analyzed with lower the better concept. This investigation shows the important and dominant factor which influences the responses of the turning operation. Research results confirmed that the responses were greatly influenced by the feed rate, followed by speed.